Human-wildlife conflicts in a crowded airspace: how can the ecological consequences of the increasing use of airspace by humans be minimized? - Lambertucci, Sergio Agustin (2015)
Over the past century, humans have increasingly used the airspace for purposes such as transportation, energy generation, and surveillance. Conflict with wildlife may arise from buildings, turbines, power lines, and antennae that project into space and from flying objects such as aircrafts, helicopters, and unmanned aerial vehicles (UAVs, or drones) (see the figure) (1–3). The resulting collision and disturbance risks profoundly affect species ecology and conservation (1, 4, 5). Yet, aerial interactions between humans and wildlife are often neglected when considering the ecological consequences of human activities.